Ampify Empayer Enterprise / Hazirah Hussin ... [et al.]. - Hussin, Hazirah; Bahador, Illya Tasnim; Mazlan, Mazni Rabiatul Adawiah; Hazman, Muhammad Naili (2025)
Ampify Empayer Enterprise, based in Cyberjaya, Selangor, specializes in manufacturing innovative, high-quality portable rotary clothes drying products under the brand Ampify CycloDry. Established as a partnership in 2021, the business aims to revolutionize the laundry drying process by offering susainable and space-saving solutions that cater to diverse customer needs. The Ampify CycloDry combines functionality, durability, and eco-friendliness with features like rust-resistant materials, foldable designs, and optional smart technology. Targeting urban families, students, and environmentally conscious consumers, the business plans to capture a share of the RM340.4 million market in Selangor by leveraging effective digital marketing strategies, competitive pricing, and unique product offerings. Financial projections show steady growth, with an estimated revenue of RM1,102,843 by the third year. This business plan outlines the company’s strategy for market penetration, operations efficiency, and financial sustainability, aiming to secure funding for expansion and innovation.